Pengaruh Pemanfaatan Fitur Voice Note Whatsapp Terhadap Komunikasi Interpersonal Mahasiswa Universitas Dharma Andalas - Refli Saputra; Yesi Elsandra ZH (CV. ITTC INDONESIA, 2026)
This study examines the influence of the voice note feature on WhatsApp toward the quality of interpersonal communication among students at Universitas Dharma Andalas. The rapid development of digital communication has shifted student interaction patterns from face-to-face communication to online-based exchanges, where voice messages are considered more expressive than text messages. This research aims to analyze the extent to which the use of the voice note feature affects interpersonal communication, measured through five key dimensions: openness, empathy, supportiveness, positivity, and equality. The study employs a quantitative approach with an explanatory design using a survey method. The research population consists of students from the 2022–2024 cohorts, with a total sample of 94 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, followed by simple linear regression to examine the causal relationship between variables. The findings indicate that the utilization of the voice note feature has a positive and significant effect on students’ interpersonal communication. This suggests that the more effectively voice messages are used in digital interactions, the higher the quality of interpersonal relationships, both in academic and social contexts. Theoretically, this study contributes to the development of interpersonal communication research mediated by digital technology. Practically, the results provide insights for students and educational institutions in optimizing digital communication features to foster more effective and meaningful interactions.